2016
DOI: 10.2355/isijinternational.isijint-2015-633
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Enrichment of P-Concentrating Phase from CaO–SiO<sub>2</sub>–FeO–MgO–P<sub>2</sub>O<sub>5</sub> Melt with Super Gravity

Abstract: In this study, the investigation on the isothermal enrichment of P-concentrating phase from CaO-SiO 2 -FeO-MgO-P 2 O 5 melt with super gravity was carried out. The results show that there was an obvious stratification appearing in the sample after centrifugal enrichment. The upper part of the sample is loose and porous, while the lower part is smooth and compact. With the help of metallographic microscopy and X-ray diffraction, it is found that the P-concentrating phase gathered in the upper part, while it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 27 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Kubo et al [11] adopted magnetic separation to remove phosphorus-enriched phases from multiphase dephosphorization slag. Li et al [12] investigated the centrifugal enrichment of P-concentrated phases from CaO-SiO 2 -FeO-MgO-P 2 O 5 melt. Wang et al [13] studied the enrichment behavior of phosphorus in CaO-SiO 2 -FeO x -P 2 O 5 molten slag, and they pointed out that a higher temperature is favorable for phosphorus enrichment from molten slag to C 2 S…”
Section: Introductionmentioning
confidence: 99%
“…Kubo et al [11] adopted magnetic separation to remove phosphorus-enriched phases from multiphase dephosphorization slag. Li et al [12] investigated the centrifugal enrichment of P-concentrated phases from CaO-SiO 2 -FeO-MgO-P 2 O 5 melt. Wang et al [13] studied the enrichment behavior of phosphorus in CaO-SiO 2 -FeO x -P 2 O 5 molten slag, and they pointed out that a higher temperature is favorable for phosphorus enrichment from molten slag to C 2 S…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in steelmaking slag, it is necessary to separate the C 2 S-C 3 P solid solution from other phases to optimize the recovery of phosphorus. Separation of C 2 S-C 3 P is achieved by already developed methods exploiting its differences from other phases, in terms of magnetic properties, 5) differences in density, 6,7) and capillary separation. 8) This study is focused on differences in the water solubility of the phases in order to selectively leach P out of C 2 S-C 3 P from the steelmaking slag .…”
Section: Extraction Of Phosphorus and Recovery Of Phosphate From Steementioning
confidence: 99%
“…It is indicated that the separation rate of solid/liquid phases has reached the maximum level and the prolonging of separation time dose no good to the separation effect. The gravity coefficient is the crucial factor for separation effect compared to separation time [23,25]. For the liquid phase, its flow trend under super-gravity field equals to the viscous resistance when the separation limitation state is reached.…”
Section: Effect Of Separation Timementioning
confidence: 99%
“…While in this study, in order to improve the flowability of liquid intermetallic compounds and keep the aluminum matrix in solid state, the separation temperature should be kept a little lower than the melting point of aluminum. Li has used the super-gravity field to separate valuable components from metallurgical slags [23][24][25]. The separation temperature in his study was usually above 1300 • C, which called high requirement on apparatus and experiment operation.…”
Section: Introductionmentioning
confidence: 99%